2007
DOI: 10.1038/sj.ejcn.1602737
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable universal salt iodization in low-income countries – time to re-think strategies?

Abstract: Although iodine content at factory level is highly variable, overall iodine supply to the population has been deemed largely sufficient. The need for perpetual iodine fortification requires reassessment of salt iodation techniques and production-monitoring systems to ensure sustainability. The emerging local technologies need evaluation as alternative approaches for sustaining universal salt iodation in low-income countries with many small-scale salt producers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…In another study, Taga et al measured large decreases in iodine concentration of salt at various points in the supply-chain and documented losses of around 44.8–82.3% (14). Similarly, different authors have described a high variability of iodine concentrations at the retailer or household levels (12, 14–16, 18–20, 24). …”
Section: Discussionmentioning
confidence: 92%
“…In another study, Taga et al measured large decreases in iodine concentration of salt at various points in the supply-chain and documented losses of around 44.8–82.3% (14). Similarly, different authors have described a high variability of iodine concentrations at the retailer or household levels (12, 14–16, 18–20, 24). …”
Section: Discussionmentioning
confidence: 92%
“…In line with this, national survey reports for Bangladesh (11), Senegal (13), and Ghana (personal communication from EF Amoaful, Ghana Health Services, 2016) indicate that subnational strata representing areas of extensive small-scale salt production had particularly low coverage of adequately iodized salt (<26% of households). The low coverage is suggested to be the result of lower technical capacity of small-scale salt producers to iodize salt, along with the increased challenges to establish effective quality assurance and regulatory monitoring of iodization in areas of widespread artisanal salt production (J Gorstein, unpublished results, 2015) (40, 41). …”
Section: Discussionmentioning
confidence: 99%
“…The Tanzanian IDD Control Program previously considered iodation of salt by manual spraying and mixing methods to be inappropriate, but the strategy of providing machine-operated salt-iodation machines to salt producers in Tanzania has been unsuccessful in the long run [ 20 ]. Nevertheless, despite failure to use iodation machines and/or breakdowns, the producers continued to manufacture iodated salt using alternative self-initiated technologies and maintained a reasonable percentage coverage of iodated salt at household level [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…An inventory of the salt-production sites[ 20 ] that had been supplied with salt iodation machines revealed that (1) most salt factories no longer used them owing to high running costs, (2) the capacity to repair breakdowns was minimal or non-existent and (3) cooperatives created to give many small-scale producers access to the equipment did not work. Both large- and small-scale producers were mainly using hand spray pumps and other small gadgets to spray potassium iodate solution on to the salt, producing highly variable iodine contents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation